Density Increase of Upper Quantum Dots in Dual InGaN Quantum-Dot Layers - Lv, Wen-Bin (文彬吕); Wang, Lai (莱汪); Wang, Jia-Xing (嘉星王); Hao, Zhi-Biao (智彪郝); Luo, Yi (毅罗) (Chinese physics letters, 2011)
Single and dual layers of InGaN quantum dots (QDs) are grown by metal organic chemical vapor deposition. In the former, the density, average height and diameter of QDs are 1.3 x 10 super(9)cm super(-2), 0.93 nm and 65.1 nm, respectively. The latter is grown under the same conditions and possesses a 20 nm low-temperature grown GaN barrier between two layers. The density, average height and diameter of QDs in the upper layer are 2.6 x 10 super(10) cm super(-2), 4.6 nm and 81.3 nm, respectively. Two reasons are proposed to explain the QD density increase in the upper layer. First, the strain accumulation in the upper layer is higher, leading to a stronger three-dimensional growth. Second, the GaN barrier beneath the upper layer is so rough it induces growth QDs